A diverse satellite DNA repertoire in Limnoperna fortunei: insights into genome structure and chromosomal organization - Castro, Jonathan Pena; Degrandi, Tiago Marafiga; Leal, Allan Oliveira; Ferreira Júnior, Augusto Luiz; Almeida, Mara Cristina de; Artoni, Roberto Ferreira (Frontiers in Molecular Biosciences, 2026)
BackgroundThe Golden Mussel, Limnoperna fortunei, represents one of the most successful aquatic invaders in South America, causing significant ecological and economic impacts. Repetitive DNA sequences, particularly satellite DNAs (satDNAs), play crucial roles in genome architecture and evolution, yet the satDNA landscape of this invasive species remains largely uncharacterized. This study aimed to comprehensively analyze the satellitome of L. fortunei using integrated computational and cytogenetic approaches.MethodsWe employed a read-clustering approach (RepeatExplorer2) to identify satDNA families from short-read genomic data. The identified families were then mapped onto the chromosome-level reference genome in silico to determine their chromosomal distribution. The physical localization of two representative satDNA families with contrasting distribution patterns was validated through fluorescence in situ hybridization (FISH) on meiotic chromosomes.ResultsOur analysis identified 129 distinct satDNA families, which were estimated to comprise approximately 9.1% of the genome based on read clustering. Subsequent in silico mapping successfully localized 126 of these families to the reference genome, where they collectively represented approximately 5.3% of the assembled chromosomes. Most families showed low divergence levels (0%–5% Kimura substitutions), suggesting recent amplification events. While most satDNAs were distributed across all 15 chromosomes, FISH analysis of two distinct families revealed contrasting distribution patterns: LfoSat025 showed preferential localization to pericentromeric regions, while LfoSat004 exhibited localized enrichment in specific chromosomal regions, demonstrating diverse organizational strategies within the satellitome. Meiotic analysis revealed normal chromosome pairing (15 bivalents), with no evidence of differentiated sex chromosomes, consistent with the species’ predominantly gonochoristic reproductive mode.ConclusionThis study provides the first comprehensive characterization of the L. fortunei satellitome, revealing a diverse and recently amplified repetitive landscape. The discrepancy between the genome-wide abundance (9.1%) and the mapped abundance (5.3%) highlights the challenges of assembling repetitive regions and underscores the value of using complementary methodologies. The identification of chromosome-specific satDNA markers establishes a foundation for developing molecular tools for invasion monitoring, including population genetic analyses to trace invasion routes and identify source populations. These findings contribute to understanding the role of repetitive DNA in genome evolution and the adaptive success of invasive species.